THE IMPLEMENTATION OF PPK-BLUD POLICY AT PUBLIC HOSPITALS OF BANDA ACEH - Andri Andri; Said Musnadi; Chenny Seftarita (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2018)
Abstract This study aimed to learn the portrayals of PPK-BLUD implementation and its obstacles at the Public Hospitals of Banda Aceh. The study employed the qualitative analysis method with the descriptive design. Primary data were used in this study. The analysis results show that all flexibilities of BLUD have been well implemented. The public perceived the post PPK-BLUD implementation service as satisfying, and good perception was also observed amid the hospital staffs. The obstacles faced in implementing PPK-BLUD were the inability of the human resources at Meuraxa Public Hospital to utilize existing business opportunities, cost inefficiency, cost differences between RSUD Meuraxa Public Hospital and INA CBG’s BPJS which resulted in a decrease in the hospital income.